Hyperconnected urban fulfillment and delivery. (January 2021) - Kim, Nayeon; Montreuil, Benoit; Klibi, Walid; Kholgade, Nitish
Highlights: A Physical Internet based urban fulfillment and delivery system is designed. Scenarios for gradual transformation show significant marginal impacts. We modeled a comprehensive system and decision architecture. We built an optimization supported agent-based simulation platform. The potential benefits of hyperconnected system is assessed via scenario analysis. Abstract: Urban last-mile delivery faces great challenges to satisfy growing customer demand with faster, punctual delivery expectations, under tight budgets and environmental requirements. The recently introduced physical internet (PI) offers a conceptual framework to address these challenges, overcoming low efficiency of current fragmented logistics operations with seamless asset sharing and flow consolidation leveraging hyperconnected systems. This article first provides a decision and system architecture for hyperconnected urban logistics, then investigates its potential at a strategic level through a simulation-based experiment in the context of large-item delivery. The results clearly demonstrate the potential of hyperconnected urban logsitics by concurrently improving often opposing measures: economic efficiency, service capability and sustainability.